Quality of Analysis Chicken Nugget with the Addition of Cheddar Cheese - Zarli, Savira Nurfadilah; Holinesti, Rahmi (Universitas Negeri Padang, 2022)
This study aims to analyze the quality of discarded layer chicken nuggets produced from the addition of cheddar cheese as much as 10%, 20%, 30% and 40% which includes shape, color, aroma, texture and taste. This type of research is a pure experiment using the Completely Randomized Design (CRD) method which has been carried out 5 treatments and 3 repetitions. The object of this research is rejected layer chicken nuggets with the addition of cheddar cheese as much as 10%, 20%, 30% and 40% of the quality of the nuggets. The types and sources of data used are primary data obtained directly from 3 expert panelists by filling out the organoleptic test format on the quality of rejected laying hens. Data analysis used ANOVA analysis (ANAVA). If the analysis of variance shows Fcount > Ftable, Duncan's test will be performed. The results showed that the addition of cheddar cheese had a significant effect on the quality of the neat shape (rectangular 6 cm x 1.5 cm x 1.5 cm), uniform shape, texture (chewy) of discarded layer chicken nuggets and on the quality of color, aroma and taste. taste has no significant effect. The results of the quality test of laying hens nuggets with cheddar cheese were the best in treatment X1 with the addition of 10% cheddar cheese.